2004
DOI: 10.1111/j.1471-4159.2004.02519.x
|View full text |Cite
|
Sign up to set email alerts
|

Metabotropic glutamate and dopamine receptors co‐regulate AMPA receptor activity through PKA in cultured chick retinal neurones: effect on GluR4 phosphorylation and surface expression

Abstract: Glutamate receptor phosphorylation has been implicated in several forms of modulation of synaptic transmission. It has been reported that protein kinase A (PKA) can phosphorylate the a-amino-3-hydroxy-5-methyl-4-isoxazolepropionate (AMPA) receptor subunit GluR4 on Ser842, both in vitro and in vivo. Here, we studied the regulation of GluR4 phosphorylation and intracellular trafficking by PKA and by metabotropic receptors coupled to adenylyl cyclase (AC), in cultured chick retinal amacrine-like neurones, which a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2005
2005
2009
2009

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 55 publications
2
17
0
Order By: Relevance
“…Consistent with these results, characterization of GluR4 subunits has revealed phosphorylation sites within the C-terminal domain of Ser 842 by CaMKII, PKA and PKC, Thr 830 by PKC in vitro, as well as phosphorylation in transfected cells of Ser 842 by PKA (Carvalho, Kameyama, & Huganir, 1999). Phosphorylation actively recruits the surface expression of GluR4-containing AMPARs in cell cultures (Gomes, Correia, Esteban, Duarte, & Carvalho, 2007;Gomes, Cunha, Nuriya, Faro, Huganir, Pires, Carvalho, & Duarte, 2004;Esteban, Shi, Wilson, Nuyriya, Huganir, & Malinow, 2003), possibly through interactions with the 4.1 family of proteins (Coleman, Mottershead, Haapalahti, & Keinanen, 2003), Arc see below), and the actin cytoskeleton.…”
Section: Synaptic Incorporation Of Glur4-containing Ampars During In supporting
confidence: 58%
“…Consistent with these results, characterization of GluR4 subunits has revealed phosphorylation sites within the C-terminal domain of Ser 842 by CaMKII, PKA and PKC, Thr 830 by PKC in vitro, as well as phosphorylation in transfected cells of Ser 842 by PKA (Carvalho, Kameyama, & Huganir, 1999). Phosphorylation actively recruits the surface expression of GluR4-containing AMPARs in cell cultures (Gomes, Correia, Esteban, Duarte, & Carvalho, 2007;Gomes, Cunha, Nuriya, Faro, Huganir, Pires, Carvalho, & Duarte, 2004;Esteban, Shi, Wilson, Nuyriya, Huganir, & Malinow, 2003), possibly through interactions with the 4.1 family of proteins (Coleman, Mottershead, Haapalahti, & Keinanen, 2003), Arc see below), and the actin cytoskeleton.…”
Section: Synaptic Incorporation Of Glur4-containing Ampars During In supporting
confidence: 58%
“…AMPA receptors are ligand-gated ion channels that are classically regulated by G-protein-coupled receptors through the activation of downstream second-messenger systems, which can involve the phosphorylation of the ligand-gated ion channel (Price et al, 1999;Snyder et al, 2000;Chao et al, 2002Chao et al, , 2003Vanhoose and Winder, 2003;Gomes et al, 2004;Mangiavacchi and Wolf, 2004). Recently, our group has demonstrated that G-proteincoupled dopamine D 1 /D 5 receptors can modulate ligand-gated ion channel NMDA/GABA A receptors through direct proteinprotein interactions, respectively (Liu et al, 2000;Lee et al, 2002a;Pei et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The relative changes in the mRNA levels of glutamate receptor subunits in cultured hippocampal neurons were determined using the (27). The non-bound biotin was removed by washing the cells with phosphate-buffered saline containing 100 mM glycine.…”
Section: Methodsmentioning
confidence: 99%